Rapid Assembly of Small Materials Building Blocks (Voxels) into Large Functional 3D Metamaterials. (22nd January 2020) - Hahn, Vincent; Kiefer, Pascal; Frenzel, Tobias; Qu, Jingyuan; Blasco, Eva; Barner‐Kowollik, Christopher; Wegener, Martin
Abstract: Herein, various 3D additive manufacturing approaches are reviewed in terms of two important figures of merit: maximum voxel printing rate and minimum voxel size. Voxel sizes from several 100 µm down to the 100 nm scale are covered. Original results on multifocus two‐photon printing at around voxel printing rates of 10 7  voxels s −1 are presented in this context, which significantly surpass previous best values. These advances are illustrated by and applied to the making of microstructured 3D (chiral) mechanical metamaterials that are composed of more than one‐hundred‐thousand unit cells in three dimensions. Previous best values for unit cells of similar complexity are smaller by two orders of magnitude. Abstract : A 3D manufacturing machine tool is presented that allows for printing rates of nearly ten million voxels per second and sub‐micrometer voxel sizes. This result is set into a broad context. As an example, it is applied to the manufacturing of 3D mechanical metamaterials with more than one‐hundred‐thousand complex unit cells and about three‐hundred‐billion voxels.